How does local mining impact on rural immigration: case of Mongolia - Amarjargal, Amartuvshin, author; Zhang, Yaoqi, author; Chen, Jiquan, author; Nutag Action and Research Institute, publisher (Colorado State University. Libraries, 2015)
After 70 years of communist regime, Mongolia chose a radical transition for democracy and a market economy in 1990. Since the 2000s, the Mongolian government has been promoting the mining industry to increase its foreign exchanges. The mining sector may offer local job opportunities and revenues, but might also cause loss and degradation of pasture land the local people depend on. An empirical study is conducted to investigate whether the immigration of rural people from a mining area is different from that of a non-mining area using a probit model based on a 2013 workforce survey of Mongolia. The result shows that mining soums receive fewer outsiders than the non-mining soums, suggesting local mining activities exert limited economic linkage in local community for a case of Mongolia.
Presented at the Building resilience of Mongolian rangelands: a trans-disciplinary research conference held on June 9-10, 2015 in Ulaanbaatar, Mongolia.
Keywords: probit model; rural immigration; mining activities; economic linkage; rural community